Risk of herpes zoster associated with JAK inhibitors in immune-mediated inflammatory diseases: a systematic review and network meta-analysis - Xu, Qingling; He, Liyuan; Yin, Yufeng (Frontiers in Pharmacology, 2023)
Janus kinase (JAK) inhibitors are a novel class of drugs that have shown efficacy in treating immunemediated inflammatory diseases (IMIDs). However, their safety profile in terms of herpes zoster infection remains unclear. We aimed to evaluate the risk of herpes zoster associated with JAK inhibitors in patients with IMIDs.A systematic search of electronic databases was conducted to identify randomized controlled trials (RCTs) that evaluated the safety of JAK inhibitors in patients with IMIDs including inflammatory bowel disease (IBD), rheumatoid arthritis (RA), spondyloarthritis (SpA), psoriasis (PsO), and psoriatic arthritis (PsA). The primary outcome of interest was the incidence of herpes zoster infection. Network meta-analysis was performed to compare the risk of herpes zoster among different JAK inhibitors and placebo.A network meta-analysis was conducted using data from 47 RCTs including 24,142 patients. In patients with IMIDs, peficitinib 100mg QD was associated with the highest risk of herpes zoster infection in patients with IMIDs, followed by baricitinib 4mg QD and upadacitinib 30mg QD. No difference in herpes zoster risk was found for other JAK inhibitors compared with placebo. Subgroup analysis indicated that higher incidence of herpes zoster was found in patients treated by baricitinib 4mg QD, peficitinib 100mg QD, and upadacitinib 30mg QD only in patients with RA.2 This is a provisional file, not the final typeset article Our study suggests that some JAK inhibitors, particularly peficitinib, baricitinib, and tofacitinib, are associated with a higher risk of herpes zoster infection in patients with IMIDs.